European Turn-of-the-century Literature and the Post-colonial Paradigm - Gjurgjan, Ljiljana Ina (Array, 1998)
The author wishes to argue that the critical paradigms invested to deal with the cultural phenomenon of colonial literature may be useful in understanding some phenomena in European turn-of-the-century literature. She demonstrates it by comparing certain features in the work of two great Irish and Croatian poets, W. B. Yeats and V. Nazor respectively, amenable to postcolonial approach by virtue of their belonging to the literature of formerly colonised countries.